2011
DOI: 10.1002/app.30705
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene‐supported N‐bromosuccinimide polymeric reagent for use in some oxidation reactions

Abstract: We report a three‐step preparation of a polymer‐supported oxidizing reagent, polyethylene‐g‐N‐bromosuccinimide (PE‐g‐NBS), through the graft copolymerization of maleic anhydride (MAn) onto polyethylene (PE) by a photochemical method with 1% benzophenone as a photosensitizer. The postgrafting treatment of polyethylene‐g‐maleic anhydride (PE‐g‐MAn) with urea on fusion gives polyethylene‐g‐succinimide (PE‐g‐succinimide), which, on further treatment with an aqueous solution of sodium hydroxide and bromine, gives t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Dhiman et al reported the use of polymer-supported NBS as an oxidizing agent . They prepared poly(ethylene- g - N -bromosuccinimide) (PE- g -NBS) through the graft copolymerization of maleic anhydride (MAn) onto polyethylene (PE) by a photochemical method with 1% benzophenone as a photosensitizer.…”
Section: Oxidation Reactionsmentioning
confidence: 99%
“…Dhiman et al reported the use of polymer-supported NBS as an oxidizing agent . They prepared poly(ethylene- g - N -bromosuccinimide) (PE- g -NBS) through the graft copolymerization of maleic anhydride (MAn) onto polyethylene (PE) by a photochemical method with 1% benzophenone as a photosensitizer.…”
Section: Oxidation Reactionsmentioning
confidence: 99%
“…In all of these applications, the advantages of the selectivity, insolubility, and reusable capacity of the polymeric reagent are taken. 18 Polymers are a large family of compounds that provide a variety of compositions and properties that can be useful in catalysis. Insoluble polymers offer suitable substrates for the heterogenization of homogeneous catalysis, but even the attachment of catalysts to soluble polymers have advantages, since being macromolecules, these polymers can easily be separated from the reaction mixture by the addition of a co-solvent or by ultrafiltration.…”
Section: Introductionmentioning
confidence: 99%